Health and Environmental Drivers of Wellbeing: A Mental Health Mediation Model in Generation Z - Bista, Barsha; Bohara, Arya (DAV Research Journal, 2025)
This paper aims to investigate how healthy living factors such as health awareness, healthy living behavior, haze pollution, healthy food choices, and physical activity influence wellbeing of Generation Z. Furthermore, the study assesses how mental health mediates the relationship between healthy living factors and wellbeing. This is a quantitative research method with correlational and causal research design. Primary data for this study were obtained through a structured, self-administered questionnaire, developed to capture comprehensive quantitative insights from Generation Z. Data were collected from 247 respondents via google form. The prepared dataset was then imported into SPSS version 20 for comprehensive statistical analysis. The findings of this research provide valuable insights into the changing well-being dynamics of Generation Z in Nepal. The results indicate that health awareness, healthy lifestyle practices, healthy food choices, and engagement in physical activities positively contribute to Gen Z’s overall well-being, while haze pollution has a significantly negative impact. Furthermore, mental health plays a moderating role in shaping this relationship. As a generation influenced by digital connectivity, easy access to information, and environmental challenges, their well-being is largely grounded in mental health, health literacy, and dietary habits. The research indicates that general lifestyle habits and environmental awareness have a lesser direct impact than expected. The study highlights that improving their well-being requires focusing on building mental resilience, providing credible health education, and supporting informed lifestyle choices. Addressing deeper psychological and informational needs is essential for enhancing the overall well-being of Nepali youth. Need for Mental health support, better health communication strategies, Holistic well-being policies. Future studies should focus on Information behavior, Perception-based health models.